Isotermas de Langmuir e Freundlich da Adsorção de Zinco por resíduos da Construção Civil Cerâmicos - Souza, André Afonso Borges de (2023)
Heavy metals, such as zinc (ZN), are inorganic compounds polluting water bodies in industrial effluents such as mining and high concentrations can have various impacts on the environment. In addition, metals are cumulative pollutants, that is, as they are exposed to the environment, they will be accumulated in the trophic chain impairing environmental quality and affecting the entire food chain of the biome. The adsorption technique is being studied and used more often for the removal of these metals present in the effluents. Thus, the objective of this work was to evaluate residues of Ceramic Civil Construction (RCCC), an alternative material, in the adsorption of the ZN metal. The study was divided into the characterization and analysis stage of the material; Batch tests to analyze the equilibrium time, pH and granulometry parameters for the optimization of kinetic parameters and evaluation of fixed bed column adsorption. The optimization parameters obtained from batch adsorption tests were: pH 7.15, 8 timeline time from 2.0 to 4.0 mm that will contribute to the higher adsorption capacity for real scale tests. The maximum adsorption capacity obtained in the langmuir method was approximately 0.116 mg/g. It was concluded that adsorption occurred in single and heterogeneous conditions.